Pengaruh Model Pembelajaran Talking Stick Berbantuan Media Atraktif Roda Pintar Terhadap Hasil Belajar Siswa kelas IV SD - Tri, Tri; Jayanti, Jayanti; Suryani, Ida (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This study aims to determine whether there is a significant influence on the learning outcomes of fourth grade students of SDN 1 Benawa who learn using the talking sticker learning model assisted by attractive smart wheel learning media. This study uses an experimental method, namely the Quasi Experimental design method used nonequivalent control group design, This type of research is quantitative with a research sample consisting of 2 classes, namely the experimental class and the control class totaling 42 students. while the population is sampled using a total sampling technique, namely a sampling technique when all members of the population are used as samples. The sample in this study was class IV A as a control class with 22 students and IVB as an experimental class with 20 students. Data collection techniques were tests and documentation. The results of the data analysis calculation obtained an average value of the experimental class of 78.50 while the average value of the control class was 61.82, The results of the hypothesis test obtained a t count of 4.209 while the t table was .684 with a sig value of 0.000 so that Ho was rejected and Ha was accepted, it can be concluded that the talking stick learning model assisted by attractive smart wheel learning media has a significant effect on student learning outcomes in social studies material at SDN 1 Benawa.